Modes of Retrotransposition of Long Interspersed Element-1 by Environmental Factors - Ishizaka, Yukihito; Okudaira, Noriyuki; Tamura, Masato; Iijima, Kenta; Shimura, Mari; Goto, Motohito; Okamura, Tadashi (Frontiers in Microbiology, 2012)
Approximately 42% of the human genome is composed of endogenous retroelements, and the major retroelement component, long interspersed element-1 (L1), comprises approximately 17% of the total genome. A single human cell has more than 5×105 copies of L1, 80 100 copies of which are competent for retrotransposition (RTP). Notably, L1 can induce RTP of other retroelements, such as Alu and SVA, and is believed to function as a driving force of evolution. Although L1-RTP during early embryogenesis has been highlighted in the literature, recent observations revealed that L1-RTP also occurs in somatic cells. However, little is known about how environmental factors induce L1-RTP. Here, we summarize our current understanding of the mechanism of L1-RTP in somatic cells. We have focused on the mode of L1-RTP that is dependent on the basic helix–loop–helix/per–arnt–sim (bHLH/PAS) family of transcription factors. Along with the proposed function of bHLH/PAS proteins in environmental adaptation, we discuss the functional linking of L1-RTP and bHLH/PAS proteins for environmental adaptation and evolution.